Financial Control System and Organizational Effectiveness of Colleges of Legal and Islamic Studies in Nigeria - Omosidi, A. S.; AbdulKareem, A. Y. (International Journal of Educational Management, 2022)
This study was a correctional research which investigated the relationship between financial control system and organizational effectiveness in Colleges of Legal and Islamic Studies in Nigeria. Purposive sampling technique was used to select eight out of the 12 Colleges of Legal and Islamic Studies that spread across three geopolitical zones of northern Nigeria. Simple random sampling techniques was used to choose 450 (84%) academic staff out of 536 in the institutions. Two researcher-designed instruments tagged Financial Control System Questionnaire” (FCSQ) and “Organizational Effectiveness Questionnaire” (OEQ) were used to collect relevant data. The instruments were validated, while Pearson product-moment correlation was used to determine their reliability, with reliability co-efficients of 0.76 and 0.79 for FCSQ and OEQ respectively. Pearson product-moment correlation was also used to test the main hypothesis and three operational hypotheses at 0.05 level of significance. The findings revealed that there was a significant relationship between financial control system and organizational effectiveness in College of Legal and Islamic Studies in Nigeria. Based on the findings the study recommended that there is the need to improve on the present financial control system/mechanism which would ensure that actual results conform to planned results in the colleges.